Pemberdayaan Masyarakat Desa Mampun Baru melalui Produksi Kombucha, Sparkling Kombucha Berbasis Bahan Lokal sebagai Minuman Fungsional (Lembaga Pengembangan Kinerja Dosen, 2026)
Mampun Baru Village possesses abundant local resources, including tea, spices, and family medicinal plants (TOGA), which have not been optimally utilized as value-added products with economic potential. This community service program aimed to improve the knowledge and practical skills of members of the Family Welfare Empowerment (PKK) group in producing Kombucha and Sparkling Kombucha as functional beverages based on local ingredients while encouraging home-based entrepreneurship and strengthening community economic empowerment. The program was implemented through socialization, demonstrations, hands-on training (learning by doing), and evaluations using pre-tests, post-tests, organoleptic assessments, and participant satisfaction questionnaires involving 15 PKK members. The results showed that participants' knowledge increased from 13.3% before the training to 93.3% after the program. The locally flavored Sparkling Kombucha achieved an average organoleptic score of 4.60, indicating very high acceptance, while participant satisfaction reached 99.4%. Overall, the program successfully enhanced participants' capacity to utilize local resources, produce functional beverages with added economic value, and develop sustainable village-based microenterprises capable of supporting local economic growth.